(untitled) (World Bulletin of Management and Law, 2024)
Disputes arising between the parties are regulated through the legal system established in the contract. The priority of law chosen in the contract is of great importance in the interpretation of the contract, in determining the rights and obligations of the parties, and in ensuring the priority of execution. This means not only the conclusion of a bilateral or multilateral contract between the parties, but also the dispute arising from it when the terms of the contract are violated. the resolution of the issue plays an important role. The field of law used when a dispute arises may also include legal norms against each other. The autonomy of the parties means the freedom of the parties to choose the law applied to them in the contract. Through this article, the rights applied to the dispute arising from the contract concluded between the parties It describes in detail the types and parties’ freedom of voluntary choice in dispute resolution. In addition, it is stated which legislation will be used to decide if the parties do not choose the right and which priority will be taken into account when faced with conflicting norms.